A Longitudinal Study of Gambling Behaviors During the COVID-19 Pandemic in Sweden - Månsson, Viktor; Wall, Håkan; Berman, Anne H.; Jayaram-Lindström, Nitya; Rosendahl, Ingvar (Frontiers in Psychology, 2021)
This study aimed to investigate changes in gambling behaviors during the first and second waves of the COVID-19 pandemic in Sweden. Participants who had gambled within the past year were recruited from social media and the Swedish National Helpline (n = 325, mean age 39.8 years, 64.8% males, 31.3% with problem gambling) and completed an online survey measuring gambling behaviors, consequences of the pandemic in general and worries related to the pandemic. A sub-sample (n = 139) completed a follow-up survey, during the second wave. The results showed no significant associations between COVID-19 consequences (financial or increased isolation) and increased monthly gambling behavior. No major migrations were observed between game types. However, gambling on a high-risk game (OR = 7.44, p < 0.001) and worrying about mental health due to the pandemic (OR = 2.85, p < 0.001) were significantly associated with past year gambling problems and increased monthly gambling problems from the first to the second wave. More longitudinal research is needed in vulnerable populations, to fully understand the long-term consequences of the pandemic.